Spatial Distribution Analysis of Total Suspended Solid (TSS) using PlanetScope Data in Menjer Lake, Wonosobo Regency - Putu Wirabumi; Pramaditya Wicaksono; Muhammad Kamal; Iwan Ridwansyah; Luki Subehi; Aan Dianto (Journal of Applied Geospatial Information, 2020)
TSS (Total Suspended Solid) is one of the optical parameters that can be used for turbidity key indicator to assess water quality. The rapid development of remote sensing technology in the field of mapping has resulted in various methods for estimating TSS concentrations. The spatial, spectral, and temporal characteristics of PlanetScope data have the potential to estimate TSS concentrations. This study aims to determine the best method for estimating TSS concentrations and mapping the spatial distribution of TSS at a depth of 0 – 0.2 m using PlanetScope data. There are 4 single bands, 12 band ratio combinations, and 4 PC-bands in TSS mapping. Single bands, band ratio combinations, and PC-band which able to pass the significance limit of r value on the number of samples (n) are used in empirical modeling of PlanetScope data with field data using regression tests. The results show that: 1) 4 band ratio combinations (B1/B4, B2/B4, B3/B4, B4/B3) and one PC-band (PC-2) significantly correlated with TSS (mg/l), 2) PC-2 is the best spectral transformation in estimating TSS concentrations in Menjer Lake, indicated by the SE value of 3.47 mg/l with maximum accuracy produced at 78.62%, 3) all models that significantly correlated are over-estimated, indicated by the variations in model plots are below the 1:1 plot line, 4) high TSS concentrations are in the north, west, and south around the edge of the lake because of the inlets and the floating net cages, while the low concentration is in the middle of the lake.